Kontribusi Komunikasi Matematik, Persepsi Siswa pada Mata Pelajaran Matematika, dan Fasilitas Belajar terhadap Hasil Belajar Matematika Siswa Kelas VII SMP Negeri 6 Purwodadi - Arimurti, Shella Aprisa, Dra. Nining Setyaningsih, M.Si (2017)
This research was conducted with the aim to, (1)mathematical communication, contribution to test perception of students in the subjects of mathematics and learning facilities against the results of the learning of mathematics, (2) test the contribution of mathematical communication against the result of learning math, (3) test the students perception of the contributions on subjects of mathematics toward mathematical learning results, (4) test facilities contribute towards the results of the learning of mathematics. Type of this research is quantitative. The population of the entire grade VII SMP Negeri 6 Purwodadi.The technique of sampling method using propotional random sampling.Now using the method of data collection and documentation. Data analysis using multiple linear regression with the significance level of 5%. The research results obtained, (1) there is a contribution to the mathematical communication, perception of students in the subjects of mathematics and learning towards the learning of mathematical results, (2) there is a contribution to the mathematical communication against the results of the learning of mathematics, (3) there is a contribution to the perception of students in the subjects of mathematics toward mathematical learning outcomes, (4) there is a learning facility contribution against the results of the learning of mathematics.